Amending polyvinly alcohol with algal biomass to enhance biodegradability - G. Aravind a/l Guru Moorthy (2023)
This paper present the likelihood for the utilization of Spirulina Algae in composite with Poly-Vinyl Alcohol (PVA). In this investigation, I have prepared an enhanced modern composite plastic films of Spirulina.